ANALYSIS OF THE METHODS OF CALCULATING THE TEMPERATURE OF THE SEMICONDUCTOR STRUCTURE OF POWER SEMICONDUCTOR DEVICES IN THE CONDITIONS OF THEIR OPERATION IN SWITCHING SEMICONDUCTOR APPARATUS - SABALAEVA, NATALIYA; ІLLARIONOV VALERII; INOSOV, SERHIY; PAVLENKO, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
In switching semiconductor devices, hybrid and contactless, power semiconductor devices are part of semiconductor switches that provide arc-free switching of electric power flows, i.e. perform the main power function of the switching device. Single-operation devices (thyristors, opto-type thyristors) or two-operation devices (IGBT-transistors, GTO-thyristors, IGCT-thyristors) are used in the mentioned above keys. The most important factor determining the reliability of this main unit of the switching semiconductor apparatus is the thermal regime of the power semiconductor device in its composition. The main parameter characterizing this mode is the temperature of the semiconductor structure of the power semiconductor device, which depends on the type of the supplied power and its design. Therefore, the calculation of the values ​​of this temperature under the specified operating conditions is one of the most important problems that arise during the development and design of switching semiconductor apparatus. The calculation of the thermal regime of a power semiconductor device used in a semiconductor apparatus is significantly complicated due to the specific form of power pulses dissipated in the semiconductor structure and the non-stationary nature of the thermophysical processes taking place in the power device. The target of this work is to develop an engineering methodology for calculating the temperature of the semiconductor structure of a power semiconductor device under the action of current pulses of an arbitrary shape with a duration of no more than 0.02 s. This target is realized by analyzing of analytical methods for calculating the temperature of the structure of power semiconductor devices, based on their simplified thermal models. The proposed method of calculating the temperature of the structure of powerful power semiconductor devices in the pulse mode allows to calculate the non-stationary thermal mode of these devices when they are affected by power pulses of arbitrary shape with a duration of up to 0.02 s. At the same time, in order to perform these calculations, it is sufficient to have information only about the parameters of power semiconductor devices, which are necessary for calculating power losses. In addition, the use of standard easy-to-use programs for calculations makes this technique accessible to a wide range of specialists.